EFEKTIVITAS PENDAPATAN LISTRIK PASCA BAYAR PADA PT. PLN (PERSERO) UNIT INDUK WILAYAH SULSELRABAR UP3 PAREPARE - MS, NURWAHIDAH (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2020)
This research method is quantitative. The data collection techniques used in this study are observation, documentation, and interviews. The data analysis technique in this study uses effectiveness ratio analysis. The conclusion of this study said that in 2014 to 2018 the percentage of effectiveness of postpaid electricity income was at a very effective level, but the percentage level of income effectiveness each period fluctuated, due to delinquent customer payments until the occurrence of losses is the amount of energy lost in the process of flowing electrical energy.